True blood. The complete second season - Minahan, Daniel; Paquin, Anna; Moyer, Stephen; Trammell, Sam; Harris, Charlaine (New York, NY : HBO Home Entertainment, 2010)
In a world where vampires are an out and vocal minority, a telepathic Louisiana barmaid falls for a century-old member of the undead who is suspected of murder.
Nothing but the blood -- Keep the party going -- Scratches -- Shake and fingerpop -- Never let me go -- Hard-hearted Hannah -- Release me -- Timebomb -- I will rise up -- New world in my view -- Frenzy -- Beyond here lies nothin'.
Based on the novels by Charlaine Harris.
Features: audio commentary; featurette.
Anna Paquin, Stephen Moyer, Sam Trammell, Ryan Kwanten, Rutina Wesley.
Originally broadcast on television in 2009.
TV rating: TV-MA.
DVDs, Dolby digital 5.1.
Keywords: Harris, Charlaine -- Television adaptations; Stackhouse, Sookie (Fictitious character) -- Drama; Vampires -- Drama; Supernatural -- Drama; Man-woman relationships -- Drama; Fiction television programs; Based on the book; Fantasy television programs; Horror television programs; Vampire television programs